The Quality of Sweet Bread with the Addition of Pumpkin - Yelvis Tanti; Kasmita Kasmita; Wiwik Gusnita; Rahmi Holinesti; Titen Darlis Santi (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Sweet bread is a popular food product widely favored across various community groups. It is known for its soft texture and sweet taste that delights the palate, making it a preferred choice for breakfast or a snack. This study aims to analyze the quality of sweet bread enriched with pumpkin based on several sensory aspects, including aroma, texture, and taste. The research method employed was experimental. The results showed that the bread quality from treatments I and III, with 100% pumpkin substitution, exhibited good volume expansion, a round and neat shape, and a yellowish-orange color characteristic of pumpkin. The texture was thin and soft, the taste was sweet, and the aroma had a distinct pumpkin fragrance.